ISOLASI DAN SELEKSI JAMUR SELULOLITIK DARI HUTAN ARBORETUM UNIVERSITAS RIAU - Hardianty, Denty Irma; Roza, R. M.; Martina, A. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The Arboretum University of Riau constitutes of a secondary forest in Pekanbaru. Manyplant genera exist in this Arboretum, therefore the litter produced has high content ofcellulosa that may provide suitable environment for many cellulolitic fungus. Thepurpose of this study was to obtain the cellulolytic fungus isolates by screening the soilthat collected from Arboretum University Riau, using Potato Dextrose Agar medium.The selection of cellulolytic fungus used Carboxyl Methyl Cellulose medium and wasindicated by the appearance of clear zona. Cellulase activities were determinated usingthe ratio of clear zone and colony diameter. The result identified 53 cellulolytic fungusisolates. The L4H4 isolate had the highest ratio (3,51). There were three ratio criterionsof clear zone to colony diameter in this study, i.e. high (24,53%), medium (35,85%) andlow (39,62%). The characterization result showed that 15 fungus isolates belonged tothe genera Aspergillus, Penicillium, Paecilomyces, Mucor and 2 isolates wereunidentified.